2023
DOI: 10.3897/bdj.11.e106418
|View full text |Cite
|
Sign up to set email alerts
|

Viability of zooplankton resting eggs in rice field sediment after pesticide applications

Abstract: Many herbicide products are commonly used in agricultural areas to prevent and eliminate weeds. Contamination from these toxicants in water might affect aquatic organisms not only in the active stage, but also in the diapause stage. To test the effect of herbicide on the resting eggs of zooplankton, we prepared two rice fields: one field without the application of pesticides (RF−NPA) and one with the application of pesticides (RF−PA) in a sampling year. We conducted a hatching experiment for 30 days. Twenty–fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Moreover, a recent study found that rice fields without pesticide applications exhibit a higher diversity of zooplankton [6,7]. In addition, besides the water column, the muddy bottom of flooded rice fields also harbours a variety of zooplankton [58].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study found that rice fields without pesticide applications exhibit a higher diversity of zooplankton [6,7]. In addition, besides the water column, the muddy bottom of flooded rice fields also harbours a variety of zooplankton [58].…”
Section: Discussionmentioning
confidence: 99%